Adequacy of school menus and national school food program requirements: a systematic review - Jacilene Alcântara Silva; Tafnes Oliveira; Isabella Ribeiro; Matheus Santos de Sousa Fernandes; Gabriela Santos (Instituto Materno Infantil de Pernambuco, 2023)
Abstract Objectives: this review aimed to evaluate the adequacy of school menus regarding the nutritional requirements of the Programa Nacional de Alimentação Escolar (PNAE) in Brazilian public schools regarding the presence of macronutrients and micronutrients and allocation of resources to purchase products from family farming. Methods: a systematic literature review was carried out using the SciELO, Bireme and Lilacs databases to select the articles. The inclusion criteria were articles that presented data on the adequacy of energy, macronutrients, micronutrients, and purchases of products from family farming during the PNAE regiment, as well as quantitative, cross-sectional, and descriptive studies carried out in the Brazilian territory. Review, editorials, letters, case studies, duplicates and those that did not assess the requirements of the PNAE were excluded. Results: at the end, 12 studies were included that showed overestimation and underestimation of nutritional adequacy in the school environment. In relation to purchases of inputs from family farming, it was observed that most of the Brazilian municipalities evaluated fulfilled the requirements for the allocation of resources. Conclusion: school menus need more supervision so that they meet the adjustments proposed by the PNAE. In addition, it is essential to promote a healthy diet that contains all the nutrients necessary to provide nutritional support for child growth and development.